Sosialisasi Mencuci Tangan untuk Anak dengan Buku Anak di PAUD Roemah Kita Yogyakarta - Monika Pretty Aprilia (TAAWUN, 2022)
This socialization departed from concerns about the lack of information for children regarding Covid-19. In addition, this socialization was held because it saw the importance of health protocols, one of which was washing hands as a measure to prevent the spread of Covid-19. Information related to health protocols has only been targeted for adult audiences. However, health protocol information for children is very limited. Parents often find it difficult to explain health protocols during a pandemic. This socialization is a collaboration with Taman Paud (Early Childhood Education) Roemah Kita in Yogyakarta as a partner. Dissemination focuses on information and knowledge related to hand washing as an important health protocol for early childhood, especially during a pandemic. Socialization was given to parents through a children's book entitled "Wash Your Hands" because of a suggestion from the government not to carry out gathering activities during the pandemic. The books are given to the parents of students. Parents then read it to the children while they are at home during the quarantine